Agents, actors, actorhood : institutional perspectives on the nature of agency, action, and authority - Hwang, Hokyu; Colyvas, Jeannette A.; Drori, Gili S. (Emerald Publishing Limited, 2019)
National governments are increasingly sharing the stage with many other forms of empowered social actors and authoritative players. Worldwide, alongside governmental bureaucracies, we witness the proliferation of non-for-profit and voluntary associations, business organizations and corporations, civic action committees and political parties, as well as celebrities and cultural icons. Importantly, whether they are individual- and collective social actors, these various actors are bestowed with the legitimate authority to speak their mind, act on their agenda, and influence the course of social progress. How might we conceptualize the role of such empowered social actors?This compilation of research and commentary gathers a range of institutional perspectives investigating what the devolution of state power and the so-called democratization of social action means for the nature of authority and how the multiplicity and variety of social actors impacts societies worldwide, extending from focus on agents to actors to actorhood.
Includes index.
Keywords: Organizational sociology -- Research.; Authority -- Research.; Social Science -- Sociology -- General.; Organizational theory & behaviour.; elektronické knihy; electronic books